Concepts and applications of finite element analysis - Cook, Robert Davis (John Wiley & Sons, 1981)
A structural mechanical approach to finite element analysis, now in a new edition. Contains over 750 problems (many of them new), introduces matrix methods early on and includes Fortran algorithms for solving numerous problems. Emphasis is physical and practical, rather than mathematical, and advanced topics such as nonlinear material behavior and structural